Meta-analysis of the efficacy and safety of rituximab in the treatment of primary Sjögren’s syndrome - Xiao Zheng; Jiaoyang Di; Xuexiao Chen; Fang Li; Yixuan Liu; Jingjing Cao; Xiaoran Ning; Lin Wei; Guimin Zheng (Frontiers in Immunology)
ObjectiveTo methodically assess the effectiveness and safety of rituximab in treating primary Sjögren’s syndrome.MethodsThe search included databases such as PubMed, Embase, the Cochrane Library, and Web of Science, covering the period from the beginning until December 2023. A meta-analysis was conducted using Stata 14.0 software.ResultsFive randomized controlled trials (RCTs) with a total of 340 patients were incorporated. The meta-analysis revealed that the group treated with rituximab had significantly lower scores in ESSPRI, pain VAS, serum IgG levels and The blood B cell level was significantly reduced, demonstrating superior results compared to the control group. However, the treatment did not effectively reduce the ESSDAI score, stimulated and unstimulated salivary flow rates and Schirmer’s test results. However, it did lead to a reduction in RF levels and enhanced complement C4 were not statistically different from the values in the control group. The occurrence of adverse events, such as infection, did not show a statistically significant difference between the two groups.ConclusionResearch has demonstrated that rituximab can decrease the levels of serum IgG and serum B cells in individuals with Sjögren’s syndrome. Additionally, it can significantly enhance the ESSPRI score and pain VAS score in patients. However, it does not have a notable impact on glandular function. The occurrence of adverse effects was like that of the control group. Given the scarcity of research, the findings may be influenced by bias, and a substantial quantity of rigorous investigations is required to validate them.